INFLUENCE OF VARIOUS WINTER WHEAT VARIETY PROPERTIES ON PRODUCTIVITY VARIABILITY - Shakaliі, S. M.; Bahan, А. V.; Yurchenko, S. O.; Golovash, L. M. (Scientific Progress & Innovations, 2022)
Every year, a large number of winter wheat varieties are entered into the State Register of Plant Varieties Suitable for Distribution in Ukraine. And the figures are constantly growing. Before choosing them, determine the parameters of the requirements for them and objectively assess the level of technological support of the economy, composition and fertility of soils, the level of their cultivation, predecessors and timing of harvest, natural and climatic zone and weather conditions of the year; take into account the spread of typical pests and pathogens in the region, because the genetic potential of the variety can be realized only if the technology meets its biological properties. The aim of the research was to evaluate the varieties of soft winter wheat according to the indicators that form the yield. To do this, the effect of the variety on the sowing properties of winter wheat grain was established; substantiated the role of the variety in the formation of wheat yields; established the main indicators of crop structure that shape plant productivity. The lowest yields were Sagaidak (5.4 t/ha), Favoritka and Smuglyanka (5.5 t/ha). It exceeded the Orzhytsia variety by 0.5 t/ha and the Bohdan variety by 0.3 t/ha. Compared to 2019, 2020 had a slightly higher yield. In the variety Sagaidak and Vilshana it increased by 0.4 t/ha. At 0.3–0.4 t/ha – in the varieties Favoritka and Smuglyanka. Bohdan variety exceeded the yield in 2019 by 0.3 t/ha. The highest yield remained in the variety Orzhytsia and amounted to 6.4 t/ha. The grain yield of winter wheat varieties in 2021 was from 5.7 to 6.3 t/ha. This year the high yields are Smuglyanka – 6.0 t/ha, Bohdan – 6.1 t/ha, Orzhytsia – 6.3 t/ha. Favorite varieties – 5.8 t/ha and Sagaidak – 5.7 t/ha have lower yields. The conducted research showed us how the variability of the elements of the structure of the harvest of winter wheat varieties is explained by the uneven moisture supply for all years of research. A necessary task is to constantly determine the variability of winter wheat productivity depending on varietal characteristics.